Structured Role-Play in Physiology Practicals: Feasibility, Acceptability, and Undergraduates Perception in a Resource Limited Setting - Akhlaq, Sana; Yousaf, Umara (Journal of Postgraduate Medical Institute, 2025)
Objective: To explore the student perceptions of structured role play as an active learning method during second-year MBBS physiology practical sessions and to obtain preliminary comparative data against traditional demonstration teaching. Methodology: An exploratory repeated measure study was accomplished from September 2024 to February 2025 at Gujranwala Medical College with 94 second-year MBBS students. The Sensory Nervous System module used regular demonstrations, while the Special Senses module employed organized role play. Lastly, the efficacy of role play was assessed using a student perception survey. OSCE checklists were developed in accordance with the curricular goals of the University of Health Sciences. The teaching strategy was hidden from the faculty examiners. SPSS v28 was used to analyze the data. Results: Role play was associated with a significant pre-to-post knowledge gain (+2.84 points, p < 0.001) whereas the traditional module showed a decline (−3.12 points, p < 0.001). OSCE scores were higher after the role-play module (6.57 ± 1.18 vs. 5.43 ± 1.07; p < 0.001). However, differences in content complexity and timing prevent causal attribution of outcomes to teaching method alone. Ninety percent of respondents recommended continuation of role play. Conclusions: Structured role play is feasible and highly acceptable to students in a resource-limited Pakistani medical college and is associated with positive learning experiences and encouraging preliminary outcomes. Ultimate superiority over traditional techniques cannot be claimed from this exploratory study.